NEW ENGLAND AND THE CHALLENGE OF INTERSTATE OZONE POLLUTION UNDER THE CLEAN AIR ACT OF 1990 - Wilcox, Geoffrey L (Boston College environmental affairs law review, 1996)
Wilcox discusses the efforts by Congress and the EPA to address interstate air pollutant transport under the Clean Air Act up to and including the 1990 Amendments and illustrates how the current Act imposes anomalous results upon states subject to ozone transport.